Safety and Immunogenicity of Chimeric Pestivirus KD26_E2LOM in Piglets and Calves - Gyu-Nam Park; Jihye Shin; SeEun Choe; Ki-Sun Kim; Jae-Jo Kim; Seong-In Lim; Byung-Hyun An; Bang-Hun Hyun; Dong-Jun An (Vaccines, 2023)
A chimeric pestivirus (KD26_E2LOM) was prepared by inserting the E2 gene of the classical swine fever virus (CSFV) LOM strain into the backbone of the bovine viral diarrhea virus (BVDV) KD26 strain. KD26_E2LOM was obtained by transfecting the cDNA pACKD26_E2LOM into PK-15 cells. KD26_E2LOM chimeric pestivirus proliferated to titers of 106.5 TCID50/mL and 108.0 TCID50/mL at 96 h post-inoculation into PK-15 cells or MDBK cells, respectively. It also reacted with antibodies specific for CSFV E2 and BVDV Erns, but not with an anti-BVDV E2 antibody. Piglets (55–60 days old) inoculated with a high dose (107.0 TCID50/mL) of KD26_E2LOM produced high levels of CSFV E2 antibodies. In addition, no co-habiting pigs were infected with KD26_E2LOM; however, some inoculated pigs excreted the virus, and the virus was detected in some organs. When pregnant sows were inoculated during the first trimester (55–60 days) with a high dose (107.0 TCID50/mL) of KD26_E2LOM, anti-CSFV E2 antibodies were produced at high levels; chimeric pestivirus was detected in one fetus and in the ileum of one sow. When 5-day-old calves that did not consume colostrum received a high dose (107.0 TCID50/mL) of KD26_E2LOM, one calf secreted the virus in both feces and nasal fluid on Day 2. A high dose of KD26_E2LOM does not induce specific clinical signs in most animals, does not spread from animal to animal, and generates CSFV E2 antibodies with DVIA functions. Therefore, chimeric pestivirus KD26_E2LOM is a potential CSFV live marker vaccine.